Comparison effect of cv 12, st 36 and st 40 ea on short term energy balance regulation in high fat diet rat - Rejeki, Purwo Sri; Harjanto, Harjanto; Argarini, Raden; Subadi, Imam (Folia Medica Indonesiana, 2017)
The aim of this study was to determine the comparative effects of EA (EA) on the CV12, ST36 and ST40 to weight gain prevention over the short-term regulation of energy balance. The study was conducted with a completely randomized design. Rats were divided into five groups: negative control group (no treatment, n=5), positive control (sham EA/back, n=5), EA CV 12 (n=6), EA ST 36 (n=6) and EA ST 40 (n=7). Rats were exposed to high-fat diet for two weeks and EA was simultaneously performed once daily, five days a week for two weeks with 2 Hz, for 10 minutes with continuous wave. Body weight, BMI, front limb circumference and rear were measured during study. Levels of blood glucose, cholesterol, triglycerides, LDL and HDL were measured at the end of the study; which reflects the short-term regulation of energy homeostasis. For weight loss, EA CV12, ST36 and ST40 group have lost weight significantly compared to the negative and positive control group. The ST40 group has a significant decrease than ST36 and CV12. The most significant decrease in BMI found in the ST40 group. EA did not affect blood glucose levels, but modulated blood lipid profile. In ST 40 group there was a significant decrease in cholesterol, LDL and triglycerides. EA at point ST 40 is potential in preventing increased body weight and BMI in rats exposed to high-fat diet compared to the CV 12 and ST 36. ST 40 is a point with a potential of lowering LDL and triglycerides serum so that it can play a role in the short term regulation of energy homeostasis but also in the prevention of dyslipidemia.